2022
DOI: 10.1002/joc.7510
|View full text |Cite
|
Sign up to set email alerts
|

The Southeast Asian monsoon and El Niño–Southern Oscillation impact on the summer atmospheric circulation of East Mediterranean during 20th century based on ERA‐20C and CMIP5 simulations

Abstract: El Niño-Southern Oscillation (ENSO) and the Indian summer monsoon (ISM) are the dominant modes of climate variability affecting the tropical and subtropical regions. In this study, we investigate the impact of ENSO episodes, through the modulation of the ISM configuration, on the Eastern Mediterranean (EMed) summer atmospheric circulation over the whole 20th century using state of the art model simulations from the 5th phase of the Climate Model Intercomparison Project (CMIP5). Results are validated against th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…A stronger ISM, therefore, should favour adiabatic heating in the EMed, which is compensated by advective cooling by stronger Etesian wind speeds. Logothetis et al (2022) analysed the relationship between wind anomalies in the EMed and the strength of the ISM over the period 1900-2000 and demonstrated that an intensified monsoon activity increases meridional wind speed in the Aegean Sea, consistent with the ISM-EMed teleconnection. This teleconnection is more prominent in extreme monsoon years often associated with the El Niño-Southern Oscillation (ENSO) (Kumar et al, 1999;Singh et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…A stronger ISM, therefore, should favour adiabatic heating in the EMed, which is compensated by advective cooling by stronger Etesian wind speeds. Logothetis et al (2022) analysed the relationship between wind anomalies in the EMed and the strength of the ISM over the period 1900-2000 and demonstrated that an intensified monsoon activity increases meridional wind speed in the Aegean Sea, consistent with the ISM-EMed teleconnection. This teleconnection is more prominent in extreme monsoon years often associated with the El Niño-Southern Oscillation (ENSO) (Kumar et al, 1999;Singh et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
“…7). Following Logothetis et al (2022), the ISM strength is approximated by the omega velocity anomalies at 200 hPa (−Pa s −1 ) averaged over the region of the strongest mean ascending motion (black boxes in Fig. 6).…”
Section: Waning Indian Summer Monsoon Reduces Summer Days With Etesiansmentioning
confidence: 99%
“…A stronger ISM, therefore, should favour adiabatic heating in the EMed, which is compensated by advective cooling by stronger Etesian wind speeds. Logothetis et al (2022) analysed the relationship between wind anomalies in the EMed and the strength of the ISM over the period 1900-2000 and demonstrated that an intensified monsoon activity increases meridional wind speed in the Aegean Sea, consistent with the ISM-EMed teleconnection. This teleconnection is more prominent in extreme monsoon years often associated with the El Niño-Southern Oscillation (ENSO) (Kumar et al, 1999;Singh et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
“…7). Following Logothetis et al (2022), the ISM strength is approximated by the omega velocity anomalies at 200 hPa (−Pa s −1 ) averaged over the region of the strongest mean ascending motion (black boxes in Fig. 6).…”
Section: Waning Indian Summer Monsoon Reduces Summer Days With Etesiansmentioning
confidence: 99%